(untitled) (Baghdad Science Journal, 2007)
The optimum conditions for production of fibrinolytic protease from an edible mushroom Pleurotus ostreatus grown on the solid medium , Sus medium, composed of Sus wastes (produced from extracted medicinal plant Glycyrrhiza glabra) were determined. Addition of 5% of Soya bean seeds meal in Sus medium recorded a maximum fibrinolytic protease activity resulting in 7.7 units / ml. The optimum moisture content of Sus medium supplemented with 5% Soya bean seeds meal was 60% resulting in 7.2 units / ml.Pleurotus ostreatus produced a maximum fibrinolytic protease activity when the spawn rate,pH of medium and incubation temperature were 2,6 and 30°C, respectively. The maximum fibrinolytic protease activity was 7.6 units / ml when incubation period of Pleurotus ostreatus at the end of 3rd week (vegetative or mycelium stage), then lowered to 6.2 and 4.4 units/ml in the end of 4th week (reproduction or fruit bodies stage) and 5th week (after harvesting of fruit bodies), respectively. Although the minimum fibrinolytic protease activity was recorded in the end of 4th and 5th weeks, production of fibrinolytic protease regard to a byproduct after harvesting of fruit bodies.